The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/antiox11050893
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Promotes the Mitochondrial Function through Activating Mitophagy

Abstract: Emerging evidence suggests that mitochondrial dysfunction mediates the pathogenesis for non-alcoholic fatty liver disease (NAFLD). Hydroxytyrosol (HT) is a key component of extra virgin olive oil which can exert beneficial effects on NAFLD through modulating mitochondria. However, the mechanism of the impacts of HT still remains elusive. Thus, an in vivo and a series of in vitro experiments were carried out to examine the impacts of hydroxytyrosol (HT) on lipid metabolism and mitochondrial function in fish. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Stress-induced mitochondrial dysfunction is prevented by PTEN-induced kinase 1 (PINK1). Ultimately, HT boosted PINK1 and AMPK expressions in the HFD zebrafish liver model, which suggested a reduction in hepatic lipid accumulation and mitochondrial dysfunction, activating the AMPK/PINK1 pathway [157].…”
Section: Hydroxytyrosolmentioning
confidence: 93%
“…Stress-induced mitochondrial dysfunction is prevented by PTEN-induced kinase 1 (PINK1). Ultimately, HT boosted PINK1 and AMPK expressions in the HFD zebrafish liver model, which suggested a reduction in hepatic lipid accumulation and mitochondrial dysfunction, activating the AMPK/PINK1 pathway [157].…”
Section: Hydroxytyrosolmentioning
confidence: 93%
“…Intestinal lipase and trypsin activities were measured by competition method using commercial kits (Nanjing Jiancheng Biological Company, Nanjing, China) according to the manufacturer’s instructions. Quantification of proteins was performed with a total protein quantitative kit (Beijing Solarbio Science and Technology Company, Beijing, China) according to our previous study [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dong et al examined hydroxytyrosol, derived from olive oil, in the setting of NASH. This study showed hydroxytyrosol can alleviate NASH by inducing mitophagy upon mitochondrial activation through the AMPK/PINK1 pathway ( Van Gisbergen et al, 2020 ).…”
Section: How Boosting Mitochondria Can Protect Liver From Covid-induc...mentioning
confidence: 98%